Revolutionizing Social Media Security: Integrating Graphic Passwords and Blockchain for Enhanced User Authentication - Lavania, Geerija; Sharma, Gajanand (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The Office of Communications and Marketing oversees various social media platforms, including "Facebook, Twitter, Instagram, LinkedIn, and YouTube." Safeguarding online presence is paramount for any business, emphasizing the crucial role of social media security. Protection measures encompass thwarting targeted phishing attacks, fortifying corporate accounts against hacking, and preventing social engineering scams. Social media platforms like Facebook and Twitter offer opportunities for fraudsters to exploit, employing legitimate but fake accounts to gain trust and extract sensitive information. Scammers adeptly craft fraudulent accounts, mimicking individuals or companies, spreading malware, online attacks, and misinformation to deceive followers and company employees into revealing private data or corporate secrets .To enhance security, an envisioned end-to-end app proposes registering mobile numbers with a password consisting of zigzag images or by sliding computer-generated images to create a unique pattern. This complements the existing module facilitating easier SIM card identification. Decentralized blockchain formed by users in communication, as opposed to a private blockchain with a central authority, is proposed. Our social media platform prioritizes two-factor authentication, requiring users to log in with their email and password, and then verifying the login request with a unique one-time password sent to their phone number during the initiation of the login request.